Give and Take : The Secret to Marital Compatibility - Harley, Willard F. (Grand Rapid Fleming H. Revell, 2000)
In GIVE AND TAKE you wll find out why you and your spouse may have lost the compatibility you started with. Then Dr. Harley will show you how to restore it, making you not only compatible, but also as much in love with each other as you ever were.
Include Appendix
Keywords: Marital conflict -- Marriage -- Married people--Psychology